What Other Communities Are Doing...National Education Goal #6 - Department of Education, Washington, DC.; Department of Education, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
Guidelines that will help individual communities reach the sixth National Education Goal are provided in this document. The goal states that by the year 2000, every American school will be free of drugs and violence and will offer a disciplined environment conducive to learning. Five stages in achieving safe and drug-free schools are outlined: (1) identify the problem; (2) engage the entire community; (3) establish and enforce strong antidrug and antiviolence policies; (4) develop a drug education curriculum and start early; and (5) train staff and provide mentors and role models. Six examples of innovative community approaches are described and 15 information resource groups are listed. (Contains 9 references.) (LMI)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Cooperation; Community Planning; Community Programs; Drug Abuse; Elementary Secondary Education; School Policy; School Safety; School Security; Violence; America 2000; Reports, Descriptive; Guides, Non-Classroom.